An Updated Systematic Review of Quantitative Studies Assessing Anxiety, Depression, Fear of Cancer Recurrence or Psychological Distress in Testicular Cancer Survivors - Rincones O; Smith A; Naher S; Mercieca-Bebber R; Stockler MR (Cancer Management and Research, 2021)
Orlando Rincones,1 Allan ’Ben’ Smith,1 Sayeda Naher,2 Rebecca Mercieca-Bebber,2 Martin Stockler2 1Centre for Oncology Education and Research Translation (CONCERT), Ingham Institute for Applied Medical Research & University of New South Wales, Liverpool, New South Wales, Australia; 2NHMRC Clinical Trials Centre, The University of Sydney, Camperdown, New South Wales, AustraliaCorrespondence: Orlando RinconesCentre for Oncology Education and Research Translation (CONCERT), Ingham Institute for Applied Medical Research & University of New South Wales, 1 Campbell Street, Liverpool, NSW, 2170, AustraliaTel +61 2 8738 9024Fax +61 2 9602 3221Email o.rincones@unsw.edu.auPurpose: A diagnosis of testicular cancer (TC) at a relatively young age can have a dramatic impact on the psychological well-being of those affected. The aim of this review was to synthesize recent evidence to provide an updated account of the prevalence, severity and correlates of anxiety, depression, fear of cancer recurrence (FCR) and distress in TC survivors.Patients and Methods: A systematic literature review was conducted from September 2017 until June 2020 using electronic databases including Embase, MEDLINE, PsycINFO, Scopus and Web of Science. Study eligibility and quality were independently assessed by two reviewers. Narrative synthesis was used to depict the severity (mean/median scores), prevalence (proportions above standard clinical thresholds) and correlates of study outcomes.Results: A total of 988 articles were identified for screening after duplicate removal. Fifty-six full-text articles were screened, and eight articles met the inclusion criteria. The reported prevalence of the outcomes varied across studies (clinical levels of anxiety ranged from 6.9% to 21.1%, depression varied from 4.7% to 7%, distress was found between 25% and 41.4%, prevalence of FCR was not reported). Few studies compared TC survivors with other populations. Correlates of poorer psychological outcomes included younger age, relationship status, employment status, poorer sexual functioning, impaired masculinity and coping strategies.Conclusion: Anxiety seems to be the most common issue for TC survivors. Men who are single or unemployed appear most at risk of poorer psychological outcomes, which seem associated with impaired masculinity and sexual function. More research is needed to identify TC survivors most likely to need one of the increasing number of psychological interventions being developed for TC survivors.Keywords: anxiety, cancer survivors, depression, distress, fear of cancer recurrence, testicular neoplasms